The Influence of Design Aesthetics on Consumers’ Purchase Intention Toward Cultural and Creative Products: Evidence From the Palace Museum in China - Li, Yang; Li, Jie (Frontiers in Psychology, 2022)
As a symbol of Chinese culture, the Palace Museum undertakes the mission of spreading Chinese culture. In recent years, through the innovative integration of traditional culture, the Palace Museum has provided ¬-a series of cultural and creative products to meet consumers’ personalized expectations, which has attracted wide attention from academia and practice. Cultural and creative products, as one of the means of cultural dissemination by museums, affect the revenue and sustainable development of museums. Thus, it is of great significance to study how consumers arrive at the decision to purchase these products. This paper explores the influence mechanism of design aesthetics on consumers’ purchase intention (N = 201). The results show that design aesthetics has a positive influence on consumers’ purchase intention through perceived value and that Chinese traditionality moderates the indirect influence of perceived value. The contributions and implications are discussed.